Myth or Reality: Perception of Frontline Managers about Diversity in Pakistan (Journal of Social Sciences Review, 2023)
Workplace diversity is a broad notion that refers to the individual variances among those who work for a company. Managing diversity in an organization is top management agenda; however, it is ineffectual to get targeted results due to manager’s perception and definition towards the concept of diversity. Middle managers are responsible in translation and implementation of diversity programs therefore their perception about diversity effects implementation and outcomes of Diversity management (DM). Pakistan has been identified homogenous and irrelevant to diversity paradigm. Contrary to that, this study has explored the value and perception of managers about diversity, exclusively responsible for implementation of diversity management practices in MNCs. Researchers introduced this area of study raising two overarching challenges: to develop more context-specific definitions of diversity; to focus on belief and value of managers about diversity effectiveness and difference in gender perception of managers; within multinational corporations. Qualitative research method has been used and eight MNCs Managers mainly handling DM functions, involve in implementation have been interviewed. Findings of study have helped to provide context based definition of diversity and difference in gender perception of managers for effectiveness of diversity and its value for company growth. Human resource managers perceive diversity mainly surface level, as gender.
Keywords: Diversity; Work Force Diversity; Human Resource Management; Gender Perception; Pakistan